Can tourism Seal the deal? : an explorative study on Seal tourism in Sweden - Alteg, Ebba (SLU/Dept. of Economics, 2019)
The increased seal populations in the Swedish coastal areas have resulted in increased damages for fishing companies with associated costs. The negative aspect of seals has been quantified (costs for small-scale fishers) but both negative and positive aspects of natural resources must be considered for politicians to make efficient policy decisions. This explorative study is a first approach to the positive aspects of the seal; seal tourism. By using an online survey is information gathered of the entire industry; characteristics of the companies, the seals’ role for the industry and the companies’ obstacles for developing their seal tourism business. The result suggest that the estimated size of the industry is approximately 56 companies and the entire industry had revenues generated from seal tourism by a total of approximately 9.85 million SEK (as of 2017). According to the study’s result, the industry’s employment corresponds to approximately 64 full-time jobs (including the owner’s work). The industry expresses that their business potential would benefit from the current size of the grey seal and the harbour seal population, which motivates license hunting. In essence, should seal management policies consider seal tourisms since it is a sustainable and profitable way of utilizing a natural resource while it also has future possibilities to contribute with employment and development in coastal areas.